Stirring up thinking - Johnson, Ben E. (Houghton Mifflin Company, 1998)
Because critical thinking skills are so interrelated that one skill depends to some degree on another, becoming adept at thinking critically involves learning to use a variety of reasoning abilities effectively in many different contexts and in many different combinations.... The wide assortment of readings included in this book have one purpose: to give you information on a variety of subjects and at a range of difficulty levels that allow you to demonstrate your grasp of one or more critical thinking skills.... In this book you will be asked to read and respond to the kind and level of materials you will typically experience during your college studies. -To the student.